2000
DOI: 10.1002/1521-3765(20001103)6:21<4034::aid-chem4034>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Dimers as Receptor Molecules for Steroid Sensors

Abstract: The dansyl-modified dimer 9 complexes strongly with the steroidal bile salts. Relative to native beta-cyclodextrin, the binding of cholate (1a) and deoxycholate (1b) salts is especially enhanced. These steroids bind exclusively in a 1:1 fashion. For other bile salts (1c-1e) both 1:1 and 1:2 complexes were observed with stabilities similar to those of native beta-cyclodextrin. This indicates that only one cavity is used, with a small contribution from the second. The difference is attributed to the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 19 publications
3
83
0
Order By: Relevance
“…Comparison with the previously reported solution data [19] for the complexation of these steroids by b-cyclodextrin reveals that the association constants in solution are higher than those at the surface. More interestingly, there is a difference in selectivity.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Comparison with the previously reported solution data [19] for the complexation of these steroids by b-cyclodextrin reveals that the association constants in solution are higher than those at the surface. More interestingly, there is a difference in selectivity.…”
Section: Resultssupporting
confidence: 51%
“…[18] A class of steroids 6 a ± 6 e whose interaction with cyclodextrins has been well studied is that of the bile salts. Their recognition by cyclodextrin derivatives has been studied both by our group [19] and by others. [20] NMR experiments have shown that these steroids are complexed through the cavity, with the aliphatic side chain of the steroid entering the cyclodextrin from the secondary Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of compounds 13 (b 2 dpa) and 14 (b 2 dans) was published elsewhere. [16] 4,4'-Bis(bromomethyl)benzophenone [55] and TBDMS-protected b-cyclodextrin [56] were prepared by literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Among the numerous guests researched, bile salts attracted much more attention because they are one kind of important surfactant-like biological amphipathic compounds possessing a steroid skeleton, which have distinctive detergent properties and play an important role in the metabolism and excretion of cholesterol in mammals [6]. For example: the thermodynamics and structure of inclusion compounds of glyco-and tauro-conjugated bile salts with CDs and their derivatives have been studied by Holm et al during the last years [7][8][9][10][11]; the interactions of different kinds of bile salts with -CD dimers linked through their secondary faces have been investigated by Reinhoudt and Vargas-Berenguel et al [12][13][14]. It has been demonstrated that the formation of inclusion complexes between CDs and guest molecules is cooperatively governed by several weak forces, such as van der Waals interactions, hydrophobic interactions, hydrogen bonding, electrostatic interactions, and every weak force does its contribution to the complexation.…”
Section: Introductionmentioning
confidence: 99%